Open signaling for ATM, internet and mobile networks (OPENSIG'98). - Campbell, Andrew T.
The ability to rapidly create and deploy new transport, control and management architectures in response to new service demands is a key factor driving the programmable networking community. Competition between service providers may hinge on the speed at which one provider can respond to new market demands over another. The notion of open programmable networks is having broad impact on service providers and vendors across a range of telecommunication sectors calling for major advances in open network control architecture, network programmability and distributed systems technology. In this paper we discuss the origins of the Open Signalling Working Group (OPENSIG) and present a summary of the fifth Workshop on Open Signaling for ATM, Internet and Mobile Networks (OPENSIG'98), which was held at the University of Toronto, Ontario, October, 1998. We also discuss a number of new initiatives in the area of open programmable networks that have recently emerged.